Toshkent viloyatida yaylov chorvachiligining rivojlanish xususiyatlari - Xalmirzaev, Axmadjan Axunovich; Kuvondikov, R.A (SCIENCE and SOCIETY, 2026)
The article analyzes the territorial features of pasture livestock development in the Tashkent region. The study examines the relationship between pasture and hayfield resources, livestock numbers, and the condition of vegetation cover. The results highlight the level of pasture resource use, the impact of livestock pressure on pasture productivity, and the directions for the efficient development of livestock farming.
Keywords: pasture livestock farming; pasture resources; hayfield resources; livestock pressure; pasture productivity; pasture ecosystems; vegetation cover